2015
DOI: 10.1016/j.jcf.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, single blind, controlled trial of inhaled glutathione vs placebo in patients with cystic fibrosis

Abstract: ClinicalTrials.gov; No.: NCT01450267; URL: www.clinicaltrialsgov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Since the early reports of impaired glutathione efflux in CF, inhaled GSH has been the focus of a number of treatment trials, which demonstrated either unsatisfactory or conflicting data with regard to improvement of lung function and decrease of oxidative stress [34][35][36][37][38][39].…”
Section: Relationship Between Glutathione Species and Markers Of Neutmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early reports of impaired glutathione efflux in CF, inhaled GSH has been the focus of a number of treatment trials, which demonstrated either unsatisfactory or conflicting data with regard to improvement of lung function and decrease of oxidative stress [34][35][36][37][38][39].…”
Section: Relationship Between Glutathione Species and Markers Of Neutmentioning
confidence: 99%
“…Inhibition of MPO would block oxidant production at the source and might help restore glutathione levels at the same time as decreasing oxidative stress. Also, long term treatment with inhaled glutathione may be beneficial, an avenue only one study has explored to date [35]. Furthermore, all studies on inhaled glutathione were done on patients older than six years.…”
Section: Relationship Between Glutathione Species and Markers Of Neutmentioning
confidence: 99%
“…Glutathione has been shown to enhance the functional activity of different immune cells against oxidative stress‐induced lung damage and is depleted in CF. Treatment with inhaled glutathione for 12 months in patients >6 years of age with FEV1 >40% predicted demonstrated no change in FEV1% predicted in patients 6–18 years of age, but improvement in those >18 years of age and in those with an FEV1 <81% predicted …”
Section: Therapiesmentioning
confidence: 96%
“…However, in CF patients, GSH levels in whole blood, blood neutrophils lymphocytes and epithelial lung fluid are markedly decreased [89]. Replenishment of GSH levels in CF has thus been investigated in a number of human studies using either inhaled GSH [90,91] or oral N-acetylcysteine, a GSH precursor [92]. These studies demonstrated the feasibility of successfully delivering GSH to human lung, with a significant improvement in lung function (FEV1), especially in patients with moderate lung disease.…”
Section: New Non-antibiotic Treatmentsmentioning
confidence: 99%